To multiply these two expressions, we will use the distributive property:
(4y^5 + 10)(4y^9 + 8y + 3) = 4y^5(4y^9 + 8y + 3) + 10(4y^9 + 8y + 3)
Now, we will distribute the terms:
= 16y^14 + 32y^6 + 12y^5 + 40y^9 + 80y + 30
Combining like terms, we get:
= 16y^14 + 40y^9 + 32y^6 + 12y^5 + 80y + 30
Therefore, (4y^5+10)(4y^9+8y+3) simplifies to 16y^14 + 40y^9 + 32y^6 + 12y^5 + 80y + 30.
(4y^5+10)(4y^9+8y+3)
3 answers
(2y^3+10)(3y^7+9y−7)
To multiply these two expressions, we will use the distributive property:
(2y^3 + 10)(3y^7 + 9y - 7) = 2y^3(3y^7 + 9y - 7) + 10(3y^7 + 9y - 7)
Now, we will distribute the terms:
= 6y^10 + 18y^4 - 14y^3 + 30y^7 + 90y - 70
Combining like terms, we get:
= 6y^10 + 30y^7 + 18y^4 - 14y^3 + 90y - 70
Therefore, (2y^3 + 10)(3y^7 + 9y - 7) simplifies to 6y^10 + 30y^7 + 18y^4 - 14y^3 + 90y - 70.
(2y^3 + 10)(3y^7 + 9y - 7) = 2y^3(3y^7 + 9y - 7) + 10(3y^7 + 9y - 7)
Now, we will distribute the terms:
= 6y^10 + 18y^4 - 14y^3 + 30y^7 + 90y - 70
Combining like terms, we get:
= 6y^10 + 30y^7 + 18y^4 - 14y^3 + 90y - 70
Therefore, (2y^3 + 10)(3y^7 + 9y - 7) simplifies to 6y^10 + 30y^7 + 18y^4 - 14y^3 + 90y - 70.